2009
DOI: 10.1111/j.1600-0706.2008.17414.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of cost of lactation in a low risk environment for a long‐lived mammal

Abstract: In a previous experiment we have documented that organisms adopt a risk‐sensitive reproductive allocation when summer reproductive investment competes with survival in the coming winter (Bårdsen et al. 2008). This tradeoff is present through autumn female body mass, which acts as an insurance against unpredictable winter environmental conditions. We tested this hypothesis experimentally on female reindeer experiencing stable and benign winter feeding conditions. Additional supplementary feeding and removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 69 publications
5
40
0
Order By: Relevance
“…In a recent study from the same study region, we found that age and body mass were highly correlated for young (·4 year) reindeer, but not for prime-aged individuals (5-13 year: Bårdsen et al 2009). We did not include females older than 13 years old so that decreased performance due to senescence was not likely to occur (see Supplement S1).…”
Section: Reproductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In a recent study from the same study region, we found that age and body mass were highly correlated for young (·4 year) reindeer, but not for prime-aged individuals (5-13 year: Bårdsen et al 2009). We did not include females older than 13 years old so that decreased performance due to senescence was not likely to occur (see Supplement S1).…”
Section: Reproductionmentioning
confidence: 80%
“…First, Tveraa et al (2003) found that especially harsh winter conditions can greatly reduce adult survival and reproductive success the following spring and summer. Second, when late winter feeding conditions are improved adult females increase their late winter body mass relative to early winter body mass (Fauchald et al 2004;Bårdsen et al 2009). This gain in body mass is, however, rapidly lost during the calving season as the diVerence in body mass is not present in the summer (Bårdsen et al 2008(Bårdsen et al , 2009Fauchald et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are nonetheless in line with previous findings showing no difference in body condition (i.e., body fat) between supplementary fed and free-ranging elk in winter (Bailey 1999). Similarly, in reindeer, positive effects of winter supplementary feeding were reported on spring but not summer or autumn body masses (Bå rdsen et al 2009). …”
Section: Effects Of Supplementary Feedingmentioning
confidence: 98%
“…Thus, body mass plays a central role for reindeer life histories and population dynamics. The effects of density and environmental fluctuations on reindeer are mostly food mediated, and supplementary feeding has been used to improve late winter condition (Bå rdsen et al 2008(Bå rdsen et al , 2009). In fact, supplementary feeding of ungulates is a common management practice used to buffer the effect of environmental stochasticity on body mass by protecting animals from winter starvation while maintaining high population densities (Fauchald et al 2004a, Putman andStaines 2004).…”
Section: Introductionmentioning
confidence: 99%